Children of Hope: The Odyssey of the Oromo Slaves from Ethiopia to South Africa, by Sandra Rowoldt Shell. Ohio University Press, 2018, 352 pages. ISBN: 978-0-8214-2318-9. Hardcover price: $49.95. - Girma, Hewan (African Human Mobility Review, 2021)
Sandra Rowoldt Shellâ€™s recounting of 64 first-person narratives of enslaved Oromo (Ethiopian) children is an innovative and well-written piece of research. As the Horn of Africa is an under-researched geographic area for the study of both domestic  and external slave trades, the plurality of these first-person slave narratives has much to teach the reader about the sensitive topic of African domestic slavery. While we can question if these accounts of the enslaved children (aged 10â€“19, with an average age of 14 at the time of the interviews) are typical, they nonetheless reveal a complicated and detailed history of slavery from the Horn of Africa.